Primerjava strukture gozdnih sestojev in sestave rastlinskih vrst v pragozdu in gospodarskem gozdu ter presoja uporabnosti izsledkov za gozdarsko načrtovanje - Bončina, Andrej (Zbornik gozdarstva in lesarstva, 2000)
Some results of comparisons of stand structure and plant species composition between virgin forest remnants and managed forests are presented. The horizontal structure of the analysed managed stands is more diverse and patchy, the number of canopy gaps and stand initiation patches is higher, and their average area is larger, too. In the managed forest growing stock is lessthan half of that in the virgin forest remnant, the volume of large diameter trees (DBH>50 cm) and dead trees (snags and logs) is much lower, treespecies composition is more diverse and tree species number in natural regeneration is higher compared to the virgin forest remnant. The herb layer is more abundant in the managed forest: more plant species were registered there and their abundance is greater. In the cyclical stand in development from juvenile to optimal phase the number and abundance of plant species increased. Proportion of developmental phases is a suitable indicator for assessment of different criteria of sustainable forest management.
Keywords: biodiversity; biodiverziteta; biotska raznovrstnost; gozdovi; pragozd